2021
DOI: 10.1002/jee.20410
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the funds of knowledge of first‐generation college students in engineering: An instrument development

Abstract: Background Students who are the first in their families to attend college are an integral part of undergraduate engineering programs. Growing bodies of research argue that educators could better support these students if they understood the unique backgrounds, experiences, and knowledge they bring with them to higher education. Purpose/Hypothesis The purpose of this article is twofold. First, we identify salient funds of knowledge used by a group of first‐generation college students in their educational and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 66 publications
(99 reference statements)
1
31
0
Order By: Relevance
“…Similarly, Smith and Lucena (2016) found that low‐income, first‐generation college students' experiences related to building, fixing, gardening, cooking, and working in low‐paying jobs provided foundational skills that were valued in engineering internships. Their later work identified social skills, like reading people, and design skills, like perspective‐taking (Verdín et al, 2021). Mobley and Brawner (2019) reported that parents' blue‐collar work experiences provided first‐generation community college transfer students with motivations to go further than their parents, as well as knowledge salient for engineering design.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Smith and Lucena (2016) found that low‐income, first‐generation college students' experiences related to building, fixing, gardening, cooking, and working in low‐paying jobs provided foundational skills that were valued in engineering internships. Their later work identified social skills, like reading people, and design skills, like perspective‐taking (Verdín et al, 2021). Mobley and Brawner (2019) reported that parents' blue‐collar work experiences provided first‐generation community college transfer students with motivations to go further than their parents, as well as knowledge salient for engineering design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With such diverse prior experiences, larger class sizes, and limited access to deeply understand students' cultures, how can faculty identify specific funds of knowledge to build upon (Smith & Lucena, 2016; Wilson‐Lopez et al, 2016)? Research suggests two primary approaches: first, faculty may develop means other than ethnographic studies to learn about their students' funds of knowledge, such as by using a survey or inventory based on prior ethnographic research (Sias et al, 2016; Verdín et al, 2021) or asking students to write reflections on their experiences in ways that prompt the students to make connections visible (Mejia & Wilson‐Lopez, 2015). This approach also addresses the issue that students may not recognize that their past out‐of‐school experiences are valuable in formal settings (Smith & Lucena, 2016; Wilson‐Lopez et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The engineering role identity development process used throughout this study includes mechanisms of interest, performance/competence beliefs, and external and internal recognition. While students' funds of knowledge are extensive, this paper focuses on seven that have been validated in prior work (Verdín et al, 2021). Our study shows that a funds of knowledge approach can provide a platform for students to incorporate their lived experiences into defining their identities within the engineering context.…”
Section: Introductionmentioning
confidence: 99%